2017
DOI: 10.1523/jneurosci.3301-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Polyribosomes in Dendritic Spine Heads, But Not Bases and Necks, during Memory Consolidation Depends on Cap-Dependent Translation Initiation

Abstract: Translation in dendrites is believed to support synaptic changes during memory consolidation. Although translational control mechanisms are fundamental mediators of memory, little is known about their role in local translation. We previously found that polyribosomes accumulate in dendritic spines of the adult rat lateral amygdala (LA) during consolidation of aversive pavlovian conditioning and that this memory requires cap-dependent initiation, a primary point of translational control in eukaryotic cells. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 72 publications
4
49
0
Order By: Relevance
“…This may indicate that ribosomes are a limiting resource in neurons, which would be consistent with stalled polysomes, sequestering many of the ribosomes in dendrites and thus making the number of ribosomes rate-limiting for basal translation. A study examining changes in polysomes after learning (Ostroff et al 2017) identified polysomes that are both sensitive and resistant to the initiation inhibitor 4EGI-1, which blocks the association of eIF4E and eIF4G, which is required for cap-dependent translation (Moerke et al 2007). In this study, the sensitive and resistant polysomes were differentially distributed at distinct types of synapses (Ostroff et al 2017).…”
Section: Regulation Of Elongation Through Eef2kmentioning
confidence: 67%
See 1 more Smart Citation
“…This may indicate that ribosomes are a limiting resource in neurons, which would be consistent with stalled polysomes, sequestering many of the ribosomes in dendrites and thus making the number of ribosomes rate-limiting for basal translation. A study examining changes in polysomes after learning (Ostroff et al 2017) identified polysomes that are both sensitive and resistant to the initiation inhibitor 4EGI-1, which blocks the association of eIF4E and eIF4G, which is required for cap-dependent translation (Moerke et al 2007). In this study, the sensitive and resistant polysomes were differentially distributed at distinct types of synapses (Ostroff et al 2017).…”
Section: Regulation Of Elongation Through Eef2kmentioning
confidence: 67%
“…A study examining changes in polysomes after learning (Ostroff et al 2017) identified polysomes that are both sensitive and resistant to the initiation inhibitor 4EGI-1, which blocks the association of eIF4E and eIF4G, which is required for cap-dependent translation (Moerke et al 2007). In this study, the sensitive and resistant polysomes were differentially distributed at distinct types of synapses (Ostroff et al 2017). It was unclear in this study, however, whether the 4EGI-1-resistant polysomes were stalled or initiated in a cap-independent (and thus 4EGI-1-independent) manner.…”
Section: Regulation Of Elongation Through Eef2kmentioning
confidence: 99%
“…Growing evidence supports the existence of polyribosomes in dendritic spines with dynamic changes during associative fear learning (Jasinska et al 2013; Ostroff et al 2017). Rough endoplasmic reticulum (RER) and trans-Golgi-like compartments have also been identified in dendrites (Pierce et al 2001), providing evidence for a satellite secretory pathway in spines.…”
Section: Contributions Of the Secreted Protein And Peptide Precursor mentioning
confidence: 88%
“…Alternatively, rpS6 may have some role independent of translation initiation (for review, see Meyuhas 2015). Compelling evidence shows that the positioning of ribosomes in spines is regulated by synaptic activity (Ostroff et al 2002) and following learning experiences (Ostroff et al 2017). For example, a recent study reveals that there are increases in polyribosomes within spines in neurons in the amygdala following aversive conditioning.…”
Section: Does Phosphorylation Of Rps6 Regulate Mrna Translation?mentioning
confidence: 99%
“…For example, a recent study reveals that there are increases in polyribosomes within spines in neurons in the amygdala following aversive conditioning. Also, infusion of the cap-dependent initiation inhibitor, 4EGI-1, disrupts training-induced polyribosome positioning and leads to decreases in polyribosomes in dendritic shafts and prevented accumulation of polyribosomes in spine heads whereas polyribosomes at spine bases were preserved (Ostroff et al 2017). A provocative idea is that phosphorylation of rpS6 via different signaling pathways may play a role in regulating ribosome trafficking in response to synaptic activity.…”
Section: Does Phosphorylation Of Rps6 Regulate Mrna Translation?mentioning
confidence: 99%